KARTAGENER’S SYNDROME: A CASE REPORT - Branco Schweitzer Mendes, Nathalia; Marim da Silveira, Renata; Zanetti Milani, Tomás; Testa, Trévor Ragnini; Mecca, Vicente Oliviecki; Bordignon, Vitória Razera; Escher, Yasmynni Weis (Clinical and Biomedical Research, 2023)
Kartagener’s syndrome is a subset of primary ciliary dyskinesia, an autosomal recessive inherited disease, and is characterized by the triad of chronic sinusitis, bronchiectasis, and situs inversus. This paper reports the case of a 27-year-old female presenting with dyspnea on medium exertion, accompanied by chronic cough, non-productive or with clear expectoration. She had recurrent pneumonia until 15 years of age and underwent a lobectomy in the lower lobe of the left lung, probably due to bronchiectasis. Chest computed tomography showed situs inversus totalis, signs of previous surgical manipulation, and mild bronchial thickening. Computed tomography of the paranasal sinuses showed signs of chronic sinusitis due to a probable ciliary kinesis disorder. These finding suggest the diagnosis of Kartagener’s syndrome. The prognosis reveals a slow rate of decline in lung function. However, repeated or chronic infections can negatively influence the quality of life of these patients.